Utvärdering av mikrobiologiska provtagningsmetoder inom ölbryggningsprocessen - Moberg, Andreas (2007)
The aim of this study was to establish knowledge about the most suitable substrate for cultivating different kinds of anaerobic beer spoilage bacteria in the brewing industry. During the study, two other aspects were investigated; if the sample volume affects the results and which anaerobic beer spoilage bacteria are present in the micro flora at the brewery. The method used was standard cultivation with four different substrates; Universal Beer Agar, Nachweismedium Bierschädliche Bakterien, Raka Ray and VLB S7-S. During the identification of bacteria in the micro flora, a method using PCR was used. None of the substrates showed a significant advantage over the others. A sample volume of 500 µl shows only 16-36 % of the colonies obtained with 100 µl sample volume, which shows that the smaller volume gives a more accurate result. The identified species were: Lactococcus lactis, Staphylococcus warneri/pasteuri, Pediococcus damnosus, Lactobacillus brevis and Lactobacillus oligofermentans. The conclusion is that Spendrups brewery should change the sample volume to 100 µl and in a future perspective, obtain laboratory equipment using PCR technology.